Paris tweets, données numériques géolocalisées et évènements urbains - Françoise Lucchini; Bernard Elissalde; Leny Grassot; Julien Baudry (Netcom)
We attempted to identify the various modes of urban events from the urban routine, and the relationship between events and the transmission of messages on the Twitter social network for Paris and the Ile de France region. The locations and rhythm of tweets emitted in this territory, reveals places with regular or others with sporadic activity. For the same urban space, there are rarely regularity in the transmitting force of a hotspot, but, on the contrary, a great variability of frequencies and rhythms, and this lack of automaticity and arrythmia make it possible to approach temporary clusters and discontinuity. According to whether the event is singular or cyclical, planned or unforeseen, whether it takes place in a single place, following a route or tends to appropriate a specific neighborhood, these tweets highlight chronotopic urban spaces.